ESP for Nurse: A Curriculum Analysis - Marleni, Lusi; Syarif, Hermawati; Zainil, Yetti (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
ESP need to be designed appropriately with the students’ need. ESP for Nurse is very important for learning English in Nursing Department. This descriptive research is taken at Nursing Department of Universitas Pahlawan Tuanku Tambusai by analyzing the curriculum; the material, teaching, and evaluation strategies used in this department. The result shows that the materials are basic medical terminology, patient communication, medical procedures, and protocols. In addition, the strategies which are used by the lecturers are active listening, empathetic communication, clear and concise communication, non-verbal communication, health literacy awareness, patient education, conflict resolution skill, interdisciplinary collaboration, time management, continuous professional development, and health and safety precautions. The learning processes are evaluated by language proficiency assessments, clinical communication simulations, written assignments and reports, case study discussions, professional presentations, interpersonal communication assessments, vocabulary and medical terminology quizzes, reflection journals, and peer and self-assessment. The curriculum is designed and managed appropriately with a nurse need.